A study on attitude and behavioral intention of generation Y towards mobile advertising / Tredia Luara Barnabas - Barnabas, Tredia Luara (Faculty of Business and Management, Universiti Teknologi MARA, 2015)
The recent development of global telecommunication becomes a new mechanism for businesses to promote their products and services and Malaysia is also seen shift to mobile taking place and thus, this growing trend cannot be ignored. Savvy businesses need to catch up with the consumer or user to stay relevant in the fast-paced environment. This modem electronic advertising concept is commercially known as mobile advertising. Today's students, members of the Y generation are digitally natives who wish, desire and might benefit from the use of mobile advertising to make purchase however their attitude towards mobile advertising remain unclear, hi conjunction to that, the main objective of this paper is to present on what is the attitude and their intention to purchase the advertised product and services. Thus, this research is based upon previous examples from academic literature and upon using a self-administrated from questionnaire applied on students from University Institute Technology MARA, Samarahan Campus.